Hemodynamic outcomes of transcatheter aortic valve implantation with the CoreValve system: an early assessment. (22nd April 2014) - da Silva, Cristina; Sahlen, Anders; Winter, Reidar; Bäck, Magnus; Rück, Andreas; Settergren, Magnus; Manouras, Aristomenis; Shahgaldi, Kambiz
Summary Background and Aims Transcatheter aortic valve implantation (TAVI) is an established method for the treatment of high‐risk patients with aortic stenosis (AS). The beneficial effects of TAVI in cardiac hemodynamics have been described in recent studies, but those investigations were mostly performed after an interval of more than 6 months following aortic valve implantation. The aim of this study is to investigate the acute and short‐term alterations in hemodynamic conditions using the echocardiography outcomes in patients undergoing TAVI. Methods and Results A total of 60 patients (26 males, 34 females; age 84·7 ± 5·8) who underwent TAVI with CoreValve system were included in the study. Echocardiography was performed before hospital discharge and at 3 months follow‐up. As expected, TAVI was associated with an immediate significant improvement in aortic valve area (AVA) (from 0·64 ± 0·16 cm2 to 1·67 ± 0·41 cm2, P‐value<0·001) and mean gradient (from 51·9 ± 15·4 mmHg to 8·8 ± 3·8 mmHg, P‐value<0·001). At 3‐month follow‐up, systolic LV function was augmented (EF: 50 ± 14% to 54 ± 11%, P‐value = 0·024). Left ventricle (LV) mass and left atrium (LA) volume were significantly reduced (LV mass index from 126·5 ± 30·5 g m−2 to 102·4 ± 32·4 g m−2; LA index from 42·9 ± 17·3 ml m−2 to 33·6 ± 10·6 ml m−2; P‐value<0·001 for both). Furthermore, a decrement in systolic pulmonary artery pressure (SPAP) from 47·5 ± 13·5 mmHg to 42·5 ± 11·2 mmHg, P‐value = 0·02 was also observed. Despite the high incidence of paravalvular regurgitation (PVR) (80%), most of the patients presented mild or trace PVR and no significant progress of the regurgitation grade was seen after 3 months. Conclusion This study demonstrates that the beneficial effects of TAVI in cardiac function and hemodynamics occur already after a short period following aortic valve implantation.